Perceived discrimination by society as mediator: relative deprivation and civic engagement of Singaporean youths - Lim, Yi Xuan (Nanyang Technological University, 2023)
Past research has yet to explore the associations between personal relative deprivation with both youths’ civic engagement attitude and their participatory behaviours in civic engagement activities in a single study. The current study proposed that perceived discrimination by society would mediate the relationship between youths’ personal relative deprivation and their civic engagement (i.e., both attitude and participation). 120 Singaporean Chinese undergraduates completed an online survey that focused on assessing their self-reported personal relative deprivation, perceived discrimination by society, civic engagement attitude, offline and online civic engagement participation. After mediation analysis, results revealed that the relationship between youths’ personal relative deprivation and their civic engagement (i.e., attitude and participation) failed to be mediated by their perception of being discriminated by society. The only significant correlations found were between perceived discrimination by society and two subscales of civic engagement attitude, after controlling for personal relative deprivation and the effects of subjective socioeconomic status. Despite the failed mediation results, these findings have theoretical implications to existing literature. More research on the relationship between personal relative deprivation and civic engagement (i.e., attitude, offline and online participation) would be essential in future studies to determine if these variables will be indirectly or directly associated.